2018
DOI: 10.1016/j.biortech.2018.02.040
|View full text |Cite
|
Sign up to set email alerts
|

The fate of trace organic contaminants during anaerobic digestion of primary sludge: A pilot scale study

Abstract: A pilot-scale study was conducted to investigate the fate of trace organic contaminants (TrOCs) during anaerobic digestion of primary sludge. Of the 44 TrOCs monitored, 24 were detected in all primary sludge samples. Phase distribution of TrOCs was correlated well with their hydrophobicity (>67% mass in the solid phase when LogD>1.5). The pilot-scale anaerobic digester achieved a steady performance with a specific methane yield of 0.39-0.92 L/gVS removed and methane composition of 63-65% despite considerable v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 45 publications
1
45
0
2
Order By: Relevance
“…Additionally, the difficult biological transformation of CBZ is provoked by the heterocyclic N-containing aromatic rings (Alvariño Pererira, 2016). The presence of chlorine atoms in DIU makes difficult its biodegradation in aerobic conditions due to an electron deficiency (Phan et al, 2018). Similar behaviour has been observed for Diazepam, which has not been analysed in this study but contains also chlorine atoms and a high consequent persistence in conventional wastewater treatments (Jelic et al, 2012;Joss et al, 2006).…”
Section: A C C E P T E D Msupporting
confidence: 76%
“…Additionally, the difficult biological transformation of CBZ is provoked by the heterocyclic N-containing aromatic rings (Alvariño Pererira, 2016). The presence of chlorine atoms in DIU makes difficult its biodegradation in aerobic conditions due to an electron deficiency (Phan et al, 2018). Similar behaviour has been observed for Diazepam, which has not been analysed in this study but contains also chlorine atoms and a high consequent persistence in conventional wastewater treatments (Jelic et al, 2012;Joss et al, 2006).…”
Section: A C C E P T E D Msupporting
confidence: 76%
“…Similar levels for some of these compounds have been reported in primary sludge samples during anaerobic digestion. 69 Carbamazepine (CAR), used as an anticonvulsant in medical therapy, was detected in all liquid digestate samples with concentrations varying from 0.07 to 5.0 mg L À1 . It has earlier been reported that CAR is unaffected by an aerobic digestion.…”
Section: Contaminants Of Emerging Concern In Liquid Digestatesmentioning
confidence: 99%
“…Complete SAC removal has also been observed in sequencing batch reactors (SBRs), where the presence of SAC had no impact on the removals of COD, ammonia nitrogen, and total nitrogen (Li et al, 2018a). In a study of primary sludge anaerobic digestion, Phan et al (2018) observed that SAC was mainly removed in the aqueous phase during anaerobic digestion. In a similar study, Buerge et al (2011) measured more than 95% SAC removal during the fermentation process, but no SAC removal from the digested sewage sludge.…”
Section: Activated Sludge/consortiamentioning
confidence: 99%